Transformation of Islamic Religious Education Learning through the SAVI Model at Elementary School in the Merdeka Belajar Era - Fedi Maulana; Feri Riski Dinata (KURAS Institute, 2025)
This study examines the transformation of Islamic Religious Education (Pendidikan Agama Islam/PAI) learning through the SAVI (Somatic, Auditory, Visual, Intellectual) model at SD Negeri 01 Pisang Baru in the Merdeka Belajar era. Employing a qualitative descriptive approach, the research explores how the SAVI model facilitates active, meaningful, and student-centered learning while promoting cognitive, affective, motoric, and spiritual development. Data were collected through interviews with the principal, PAI teachers, and students, complemented by classroom observations and document analysis. Findings indicate that the SAVI model enhances student engagement, motivation, and comprehension by integrating physical movement, auditory, visual, and intellectual activities into learning. However, challenges remain, including limited facilities, media resources, and the need for continuous teacher training. The study highlights the importance of aligning pedagogical innovation with Islamic educational values and contemporary curricular policies. Practically, it provides guidance for educators to implement multisensory approaches effectively and for schools to support sustainable pedagogical transformation. This research contributes to the discourse on active, embodied, and multisensory learning in Islamic Religious Education (Pendidikan Agama Islam/PAI), offering insights for policy makers, practitioners, and future research.